Mazurki fortepianowe Teodora Leszetyckiego - Nidecka, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Teodor Leszetycki (1830–1915) became famous as a teacher of the piano arts. Most of his life he spent in Vienna. He developed his own piano playing method, which gained recognition all over the world. However, he was also a composer. His work encompasses main piano pieces. Leszetycki’s Mazurkas are a minority among his works. He created only nine pieces of this genre. The main features of his Mazurkas are: a significant textural and dynamic-expressive contrast in the space of short musical fragments, the lack of cantilena in motifs and numerous virtuoso inserts. Leszetycki's style in his Mazurkas can be described as classical-figurative, with a clear influence of his Viennese teacher and composer Carl Czerny and Ferenc Liszt, in the meaning of the masculine style of piano playing. They show the composer as a great pianist who used an excellent piano technique. To sum up, the Mazurkas of Teodor Leszetycki were perceived more as an art of general use than highly artistic.
Piano Mazurkas by Teodor Leszetycki
Keywords: Teodor Leszetycki; piano mazurka; romantic miniature